Investigations into electrical discharges in gases - Kliarfeld, B. N. (Boris Nikolaevich), 1904- (Pergamon Press : [Distributed in the Western Hemisphere by Macmillan pursuant to a special arrangement with Pergamon Press], 1964)
Investigations into Electrical Discharges in Gases is a compilation of scientific articles that covers the advances in the investigation of the fundamental processes occurring in electrical discharges in gases and vapors. The book details the different aspects of the whole life cycle of an arc, which include the initiation of a discharge, its transition into an arc, the lateral spread of the arc column, and the recovery of electric strength after extinction of an arc. The text also discusses the methods for the dynamic measurement of vapor density in the vicinity of electrical discharges, alon.